NUMBERED-HEAD TOGETHER IN TEACHING READING NARRATIVE - Ramadhanty, Anisa; Ruyani, Yayan; Syahrizal, Trisnendri (PROJECT (Professional Journal of English Education), 2019)
Reading comprehension is needed by students in order to have a good reading skill. In this journal, the researchers are trying to examine the implementation of NHT technique in improving students’ reading comprehension of narrative text. Quantitative used as the research method with pre-experimental research design. There are three stages in conducting pre-experimental design. First, students are given pre-test to measure their knowledge. Second, students are given the treatment and last, students are given posttest after using NHT technique. In conducting the data, the researchers spend seven times consisted of pretest, posttest, and five times treatments. As the result, the mean score of pre-test is 43.58. After implementing NHT technique in every meeting, reading comprehension of students had been getting better, it can be seen in average of the mean score of post-test became 62.45. It can be concluded that NHT technique can improve students’ reading comprehension.Keywords:  Numbered-head together, Students’ reading comprehension